2019
DOI: 10.1111/joim.13012
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic features of vascular calcification in chronic kidney disease

Abstract: Background Patients with chronic kidney disease stage 5 (CKD5) are predisposed to vascular calcification (VC), but the combined effect of factors associated with VC was sparsely investigated. We applied the relaxed linear separability (RLS) feature selection model to identify features that concomitantly associate with VC in CKD5 patients. Methods Epigastric arteries collected during surgery from living donor kidney transplant recipients were examined to score the histological extent of medial VC. Sixty‐two phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…An additional feature of atherosclerosis is calcification, which is often advanced among CKD patients. We recently reported that IgM anti-PC is a protection marker for vascular ageing where calcification was one included feature [48]. However, it is not known if anti-PC could play a role in different stages of calcification.…”
Section: Discussionmentioning
confidence: 99%
“…An additional feature of atherosclerosis is calcification, which is often advanced among CKD patients. We recently reported that IgM anti-PC is a protection marker for vascular ageing where calcification was one included feature [48]. However, it is not known if anti-PC could play a role in different stages of calcification.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 62 (37.1%) original investigations reported gender-associated adjusted risk of having higher prevalence/severity of VC among patients with CKD [40,42,44,47,48,58,[63][64][65]67,68,84,86,88,90,93,95,[100][101][102]106,112,113,116,117,. Among these articles, 17 (27.4%), 40 (64.5%) and 5 (8.1%) included patients with nondialysis CKD, dialysis-dependent CKD, and renal transplant recipients, respectively (Supplementary Table S2).…”
Section: Gender-related Differences In the Adjusted Risk Of Ckd-associated Vc Presence Or Severitymentioning
confidence: 99%
“…Expanded Materials and Methods Figures S1-S12 Tables S1-S10 Dataset 1-3 Major Resources Table References 12,[17][18][19][28][29][30][31]63,64 Uncut Gel Blots…”
Section: Disclosuresmentioning
confidence: 99%